Pengaruh Penggunaan Tepung Biji Durian (Durio zibethinus Murr) Terhadap Cemaran Mikroba, dan Daya Hambat Escherichia coli, Staphylococcus aureus dan Salmonella sp. Salami - Sofi Sembor; Nova Lontaan; Youdhie Kowel; Stelly Novaria Rumerung (Universitas Sam Ratulangi, 2024)
The aim of this research was to determine the effect of adding durian seed flour (Durio zibethinus Murr) on microbial contamination and the inhibitory power of Escherichia coli, Staphylococcus aureus and Salmonella bacteria in salami products. The materials used are durian seed flour, laying hens, spices, bacterial cultures of Lactobacilus plantarum and Lactobacilus acidophylus. The research used a Completely Randomized Design with 5 treatments and 4 replication P0(0%), P1(5%), P2(10%), P3(15%) and P4(20%). The parameters measured include the level of microbial contamination and the inhibitory power of Escherichia coli, Staphylococcus aureus and Salmonella bacteria. The research data were analyzed using ANOVA and continued with the Honestly Significant Difference Test. The research results showes that the level of escheria coli, Stapilococcus aureus and Salmonella contamination in salami products were negative for each sample. The results of the Inhibition Test on the growth of Escherichia coli bacteria for each treatment P0, P1, P2, P3 and P4 formed an inhibitory zone with an average diameter of 1.11mm; 2.67mm; 2.59mm; 2.01mm and 1.25mm although statistically there was no significant difference (P>0.05). The inhibitory power of Staphylococcus aureus bacteria with an average diameter of 1.19cm, 2.51cm, 2.56cm, 1.86cm, 0.89cm; Inhibition power of Salmonella bacteria 0.91cm; 1.14cm; 0.72cm; 0.42cm and 0.06cm